2016
DOI: 10.2337/db15-0917
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Deletion of α1AMPK Exacerbates Atherosclerosis in LDL Receptor Knockout (LDLRKO) Mice

Abstract: Macrophage inflammation marks all stages of atherogenesis, and AMPK is a regulator of macrophage inflammation. We therefore generated myeloid α1AMPK knockout (MAKO) mice on the LDL receptor knockout (LDLRKO) background to investigate whether myeloid deletion of α1AMPK exacerbates atherosclerosis. When fed an atherogenic diet, MAKO/LDLRKO mice displayed exacerbated atherosclerosis compared with LDLRKO mice. To determine the underlying pathophysiological pathways, we characterized macrophage inflammation/chemota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 47 publications
3
34
2
Order By: Relevance
“…In fact, we found that metformin protected against hyperglycemia-induced atherosclerosis through AMPK␣2 activation, which has no effect on monocyte differentiation (41). In contrast with a reduced atherosclerosis observed in this study, Cao et al (42) reported that myeloid AMPK␣1-deleted LDL receptor knock-out mice (Ldlr Ϫ/Ϫ ) increased formation of atherosclerotic plaque with enhanced macrophage inflammation and higher plasma triglyceride and cholesterol content. Although ApoE Ϫ/Ϫ and Ldlr Ϫ/Ϫ mice have been used extensively as two mouse models of atherogenesis, Ldlr Ϫ/Ϫ mice have much lower plasma cholesterol levels and develop less severe atherosclerotic lesions than ApoE Ϫ/Ϫ mice on a normal chow diet (43,44).…”
Section: Parametercontrasting
confidence: 99%
“…In fact, we found that metformin protected against hyperglycemia-induced atherosclerosis through AMPK␣2 activation, which has no effect on monocyte differentiation (41). In contrast with a reduced atherosclerosis observed in this study, Cao et al (42) reported that myeloid AMPK␣1-deleted LDL receptor knock-out mice (Ldlr Ϫ/Ϫ ) increased formation of atherosclerotic plaque with enhanced macrophage inflammation and higher plasma triglyceride and cholesterol content. Although ApoE Ϫ/Ϫ and Ldlr Ϫ/Ϫ mice have been used extensively as two mouse models of atherogenesis, Ldlr Ϫ/Ϫ mice have much lower plasma cholesterol levels and develop less severe atherosclerotic lesions than ApoE Ϫ/Ϫ mice on a normal chow diet (43,44).…”
Section: Parametercontrasting
confidence: 99%
“…In addition, anti-inflammatory agents, such as salicylate and methotrexate, activate AMPK 19,222 , while pro-inflammatory stimuli (for example, lipopolysaccharide and TNF) suppress AMPK activity by increasing protein phosphatase activity and through inhibitory phosphorylation 209,223,224,225 , collectively supporting the concept that AMPK plays a vital role in mediating the balance between pro-inflammatory and anti-inflammatory stimuli 226,227 . The ability of AMPK to suppress multiple inflammatory pathways (for example, NF-κB, the NLRP3 inflammasome and ER stress) in response to numerous distinct stimuli suggests that AMPK suppression of inflammatory programmes may be mediated in part through regulation of key tenets controlling cellular metabolism such as mitochondrial function, mitophagy and/or autophagy and fatty acid oxidation, all of which have been shown to regulate inflammatory pathways [219][220][221]228 . Additional levels of control may also involve the circadian clock, which is vital for regulating immune cell function 203 and is controlled through AMPK phosphorylation of cryptochrome 1 (REF.…”
Section: ) (Table 1)mentioning
confidence: 99%
“…In addition to lowering LDL-C, AMPK activation in response to salicylate and A769662 enhances reverse cholesterol efflux from macrophages owing to upregulation of the transport proteins ATP-binding cassette subfamily A member 1 (ABCA1) and ABCG1 (REFS 249,250 ), or by increasing scavenger receptor class B type 1 (SRB1)-mediated hepatic delivery 246 . AMPK suppression of macrophage inflammation within plaques 228,230,251 and adipose tissue 219 may also be important for suppressing atherosclerosis development. In addition to regulating macrophage polarization, increased proliferation of monocytes to macrophages and reductions in autophagy are important for atherosclerosis 252 , and in this regard, AMPK inhibition of cellular proliferative pathways such as mTOR and p53 as well as the induction of autophagy would be expected to reduce atherosclerosis progression 253 ; however, this has not been observed in all studies 254 .…”
Section: ) (Table 1)mentioning
confidence: 99%
“…Deletion of myeloid AMPK signaling does not alter monocyte populations: While AMPKα1 is the predominant isoform expressed in haematopoietic cells 12,20 , myeloid deficiency of either AMPKα1 or AMPKα2 has been shown to alter atherosclerosis [15][16][17] .…”
Section: Resultsmentioning
confidence: 99%
“…Myeloid AMPK signaling does not alter the amount of CD68+ cells: Deletion of myeloid AMPK on an ApoE-deficient 16 or LDLr-deficient 17 background resulted in less and more markers of macrophage accumulation, respectively. To interrogate this in our model, we used CD68 as a general marker of macrophage-like cells within atherosclerotic lesions, since it is now well established that vascular smooth muscle cells can adopt CD68 expression as atherogenesis progresses 27 .…”
Section: Myeloid Ampk Does Not Regulate Systemic Inflammation During mentioning
confidence: 99%